Sifat Fisik Beton Pulih Mandiri Dengan Memanfaatkan Bakteri Bacillus Subtilis - Widika Arfa A; Zulfikar Djauhari; Enno Yuniarto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
As the technology evolves, the utilization of micro-organisms such as bacteria has been developed and used as concrete mixtures. This was inspired by the ability of the bacteria which is able to repair the cracks on concrete, as known as self healing concrete. Therefore, properties of self healing concrete needs to be reviewed. This research used bacillus subtilis chemical solution with amount of 25 ml and with the concentration of 105 cells/ml. Research methodology consisted of adding bacteria solution on concrete mixtures. Cylinder compressive tests were initiated on normal concrete and bacterial concrete on age of 28 days and 56 days. Physical property of concrete was evaluated according to its workability, porosity, and shrinkage rate. The results showed that the slump on bacterial concrete was 80 mm. This indicated bacterial concrete had lower consistency than normal concrete. Porosity results on bacterial concrete was better with deviation of 11,241% compared to normal concrete on age of 28 days and low rate of shrinkage, i.e. 61,50 µm. Hence, it could be concluded that physical properties of self healing concrete is better than normal concrete.Keywords : bacillus subtilis bacteria, self-healing concrete, physical properties ofconcrete